2020
DOI: 10.1016/j.fgb.2020.103432
|View full text |Cite
|
Sign up to set email alerts
|

Carbon metabolism and transcriptome in developmental paths differentiation of a homokaryotic Coprinopsis cinerea strain

Abstract: The balance and interplay between sexual and asexual reproduction is one of the most attractive mysteries in fungi. The choice of developmental strategy reflects the ability of fungi to adapt to the changing environment. However, the evolution of developmental paths and the metabolic regulation during differentiation and morphogenesis are poorly understood.Here, we monitor the carbohydrate metabolism and gene expression regulation during the early differentiation process from the "fungal stem cell", vegetative… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 111 publications
1
36
0
Order By: Relevance
“…In Coprinopsis cinerea, major differences in carbohydrate metabolism and carbohydrate redistribution were observed during fungal development, from vegetative growth to conidiation, fruiting, and sclerotia formation under different environmental conditions (Xie et al, 2020). Such balancing processes were internally regulated by regulatory genes and metabolic genes with high flexibility (Wang et al, 2019;Xie et al, 2020).…”
mentioning
confidence: 99%
“…In Coprinopsis cinerea, major differences in carbohydrate metabolism and carbohydrate redistribution were observed during fungal development, from vegetative growth to conidiation, fruiting, and sclerotia formation under different environmental conditions (Xie et al, 2020). Such balancing processes were internally regulated by regulatory genes and metabolic genes with high flexibility (Wang et al, 2019;Xie et al, 2020).…”
mentioning
confidence: 99%
“…Genome annotation of the draft genome was done using funannotate v1.7.2, following the workflow of clean-sort-mask-train-predict-update-annotate (Palmer and Stajich, 2019). A total of 18 transcriptomes was acquired from NCBI BioProject PRJNA573620 (Xie et al, 2020) and used to help training models for gene prediction and annotation. The RNA-seq data were quality filtered using fastp with default parameters, including the window size of 4, mean quality of Q 20 and minimum read length of 15 nt (Chen et al, 2018).…”
Section: Gene Prediction and Genome Annotationmentioning
confidence: 99%
“…Eighteen transcriptomes, including developmental stages of vegetative mycelium, oidiation, sclerotia formation, hyphal knots, primordia and young fruiting bodies (Xie et al, 2020), were used to support the genome annotation. A total of 15,250 genes was predicted in the genome, with 16,862 transcripts.…”
Section: Gene Prediction and Functional Annotationmentioning
confidence: 99%
“…It was also showed that carbohydrate metabolism has an essential role in the initiation of the fruiting body (Brunt and Moore, 1989). Changes in expression of genes associated with glycogen metabolism were shown through the development of C. cinerea (Krizsán et al, 2019;Xie et al, 2020). Furthermore, the accumulation of glycogen in the basal region of the secondary hyphal knot was also observed (Matthews and Niederpruem, 1973;van der Valk and Marchant, 1978).…”
Section: The Background Of Phylogenetic Comparative Methods Used In This Studymentioning
confidence: 93%
“…Among coprinoid species, Coprinopsis cinerea became a model mushroom, having a plethora of genetically modified mutants strains (Kües, 2000) and it was among the first fungal genomes which were sequenced (Stajich et al, 2010). Thanks to genetic and bulk RNA-seq analyses of C. cinerea, our knowledge on the genetic background of mushroom development have been further widened (Plaza et al, 2014;Muraguchi et al, 2015;Krizsán et al, 2019;Xie et al, 2020).…”
Section: The Background Of Phylogenetic Comparative Methods Used In This Studymentioning
confidence: 99%